2014
DOI: 10.3171/2013.11.jns13952
|View full text |Cite
|
Sign up to set email alerts
|

Inducing transient language disruptions by mapping of Broca's area with modified patterned repetitive transcranial magnetic stimulation protocol

Abstract: The stimulation paradigm with the modified patterned nTMS protocol was shown to be promising and might gain more widespread use in speech localization in clinical and research applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…7,23,35,40 At present, however, very few data are available on the use of HFMS for language mapping. Previous works employing transcranial magnetic stimulation and grid electrodes 3,32 have described the use of HF stimulation over the Broca's area producing speech arrest rendered results similar to those observed with LF stimulation. Our study confirmed these observations intraoperatively.…”
Section: Discussionmentioning
confidence: 66%
“…7,23,35,40 At present, however, very few data are available on the use of HFMS for language mapping. Previous works employing transcranial magnetic stimulation and grid electrodes 3,32 have described the use of HF stimulation over the Broca's area producing speech arrest rendered results similar to those observed with LF stimulation. Our study confirmed these observations intraoperatively.…”
Section: Discussionmentioning
confidence: 66%
“…There is evidence in earlier studies for the justification of both PTIs. 30,55,63,81 Thus, our protocol was modified after 25 patients.…”
Section: Methodsmentioning
confidence: 99%
“…We have successfully applied recently developed methodology in healthy subjects [6][7][8] for mapping the M1 for laryngeal muscles and opercular part of Broca's area in the first patient with tumor in the frontal cortex of the left hemisphere invading the Broca's area and the lateral part of the M1 cortex. The findings of preoperative nTMS served the neurosurgeon as the guide for planning the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies used rTMS as a virtual lesion model to investigate the contribution of specific cortical areas to language processing by inducing various types of language errors [4,5]. Recently our group developed the nTMS methodology along with the intraoperative methodology for mapping motor speech related cortical areas (primary motor cortex (M1) for laryngeal muscles and caudal opercular part of inferior frontal gyrus (corresponding to Broca's area) by recording evoked potentials from laryngeal muscle [6][7][8]. The modified patterned rTMS protocol was used to map the M1 for laryngeal muscles while recording corticobulbar motor evoked potentials (CoMEPs) from cricothyroid muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation